A CRITICAL ANALYSIS OF THE FILM MAKING TECHNIQUES OF TRIVIKRAM SRINIVAS - Kulkarni Pranav Bharadwaj, Prof. S. Santosh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Trivikram Srinivas, a remarkable Telugu filmmaker, has shaped a niche for himself through his unique and exclusive filmmaking techniques. This critical analysis dives into the mixed aspects of Srinivas's cinematic style, exploring his storytelling skill, visual aesthetics, and directorial choices that contribute to his films' extraordinary flavor. Srinivas is honored with the title “Guruji” for his exceptional storytelling, often characterizedby smart and comic dialogues that resonate with the audiences. He has the potential to blend humor flawlessly with emotional depth, establishing a narrative style that engages viewers ondifferent levels. This abstract investigates Srinivas’s directorial choices, looking at his signature techniques and how they contribute to the overall impact of his films. Whether his creative use of music, expert handling of casts, or the fusion of cultural shades. Srinivas’s stories are generally hero-centric and the scripts often glorify heroes with his regular touch of philosophic elements. He usually molds several parts of the story to upraise certain scenes. He is a master of words as weapons and making the audiences cry just with the appropriate usage of words and is knownas the “Wizard of Words” " who can swine people's minds just by using words. Furthermore, the study critically upraises the evolution of Srinivas’s filmmaking technique throughout his films, taking into consideration how external influences and industry trends have carved his approach. By exploring the strengths and potential limitations of his filmmaking styles, this study provides an extensive understanding of Trivikram Srinivas’s contribution to filmmaking, offering invaluable insight into the different shades of his work and experiencing his presence in the Telugu cinema.